Biocompatible Nanogenerators through High Piezoelectric Coefficient 0.5Ba(Zr0.2Ti0.8)O3‐0.5(Ba0.7Ca0.3)TiO3 Nanowires for In‐Vivo Applications. (25th September 2014) - Yuan, Miaomiao; Cheng, Li; Xu, Qi; Wu, Weiwei; Bai, Suo; Gu, Long; Wang, Zhe; Lu, Jun; Li, Huanping; Qin, Yong; Jing, Tao; Wang, Zhong Lin
<x xml:space="preserve">Abstract</x> Lead‐free BZT‐BCT (0.5Ba(Zr0.2Ti0.8)O3‐0.5(Ba0.7Ca0.3)TiO3) nanowires with a high piezoelectric coefficient are synthesized and nanogenerators (NGs) composed of them are successfully developed. The studied in vitro and in vivo biocompatibility of the NGs shows great potential for their application as in vivo power sources. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>